2022
DOI: 10.1111/nmo.14313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intestinal microbiota transplantation on cerebral ischemia reperfusion injury in aged mice via inhibition of IL‐17

Abstract: Objectives This study investigates the effects and mechanisms of intestinal microbiota transplantation on cerebral ischemia reperfusion injury in aged mice. Methods We constructed a middle cerebral artery occlusion model after fecal microbiota transplantation from young C57 mice to aged C57 mice for 30 consecutive days via enema. The neurological deficit score, cerebral infarction volume, fecal flora composition, and IL‐17 levels in the colon, brain, and serum were evaluated in young mice, aged mice, and aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…IL‐17 has been known to be largely expressed by activated T cells and is involved in host innate immune responses. More importantly, numerous studies have provided evidence that IL‐17‐producing CD4+T cells play a critical role in organ rejection and IRI in the heart, brain, and liver 8,21,22 . Data from the study conducted by Wang et al 23 demonstrated that IL‐17 was involved in the inflammatory response of IRI in acute kidney injury, and inhibition of IL‐17 might be a novel therapeutic strategy for the treatment of acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐17 has been known to be largely expressed by activated T cells and is involved in host innate immune responses. More importantly, numerous studies have provided evidence that IL‐17‐producing CD4+T cells play a critical role in organ rejection and IRI in the heart, brain, and liver 8,21,22 . Data from the study conducted by Wang et al 23 demonstrated that IL‐17 was involved in the inflammatory response of IRI in acute kidney injury, and inhibition of IL‐17 might be a novel therapeutic strategy for the treatment of acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies suggest that HFD may cause the abnormality of intestinal flora and contribute to ischemic stroke via the activation of inflammation reactions (Rothhammer et al 2018, Sampson et al 2016, Singh et al 2016. A recent study showed that FMT could restore the abnormality of intestinal flora and attenuated ischemic stroke injury in aged mouse model (Feng et al 2022). However, the efficacy of FMT on ischemic stroke in obese population remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) has become an effective gut microbiota intervention approach for the treatment of a variety of diseases (Vendrik et al 2020). A recent study reported that FMT could alleviate cerebral ischemia reperfusion injury in aged mice (Feng et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…After 30 days of continuous gavage of fecal flora from young mice to aged mice, researchers established the tMCAO model. They found significant reductions in IL-17 levels in serum, colon, and brain tissue, reduced infarct volumes, and improved neurological function [ 104 ]. Indole-3-propionic acid (IPA), a tryptophan (Trp) catabolic product produced by intestinal flora, is reduced in the serum of MCAO mice.…”
Section: Targeting Th17 Cells and Il-17a In Treatment Of Ischemic Strokementioning
confidence: 99%